Relationship between blood lipid profiles and pancreatic islet β cell function in Chinese men and women with normal glucose tolerance: a cross-sectional study - Zheng Tianpeng; Gao Yun; Tian Haoming (BMC, 2012)
Abstract Background Dyslipidemia is present in people with diabetes as well as subjects with normal glucose tolerance (NGT). The purpose of this study was to investigate the relationship between lipid profiles and β cell function in Chinese individuals with NGT but without history of diabetes or prediabetes. Methods A total of 893 men and 1454 women aged 18-76 years living in Sichuan, China, who were not being treated with lipid-lowering drugs were enrolled in this study. Insulin sensitivity (IR) was evaluated using the homeostasis model assessment -IR (HOMA-IR), β-cell function was calculated by the following equation: ΔI30/ΔG30/ HOMA-IR (ΔI30/ΔG30: the ratio of incremental glucose and insulin 30 min after glucose intake). Multivariate linear regression analyses were performed to estimate the relationship between blood lipid and β cell function as standardized coefficients (β). Results β cell function decreased in men and women with increasing age. We found inverse relationships between β cell function and total cholesterol (TC) in men and women (β = −0.157 and −0.113, respectively, both p < 0.001), low-density lipoprotein-cholesterol (LDL-C; β = −0.130 and −0.068, respectively, both p < 0.001), TC/high-density lipoprotein-cholesterol (HDL-C) ratio (β = −0.084, p < 0.01 and −0.096, p < 0.001), and triglycerides (TG) (women only; β = −0.053, p < 0.05). However, β cell function was not associated with HDL-C in men or women (β = −0.034 and 0.000, respectively, both p > 0.05) or the TG/HDL-C ratio (β = −0.035 and −0.013, respectively, both p > 0.05). β cell function was significantly worse in males than in females in all age groups, except in subjects aged > 70 years. Conclusions Dyslipidemia is associated with dysfunction of pancreatic β cells in subjects with NGT and this is particularly evident in people with elevated TC and LDL-C levels, especially males. Trial Registration Number #TR-CCH-Chi CTR-CCH-00000361